Can the application of simple pre-germination treatments maximize caatinga seeds germination? (Research, Society and Development, 2024)
In the semi-arid region, seeds present mechanisms of integumentary dormancy, a protection method that prevents germination in periods unfavorable for their development. This condition can make the process of obtaining seedlings difficult. Therefore, this work sought to evaluate the efficiency of applying pre-germination treatments to seeds of Amburana cearensis (German) A.C.Sm., Astronium urundeuva (M. Allemão) Engl., Senna spectabilis (DC.) H. S. Irwin & Barneby and Poincianella pyramidalis (Tul) L. P. Queiroz. The study was carried out at the Serra Talhada Academic Unit, between the period of September 9th to November 17th, 2022. Seeds of amburana-de-cheiro, aroeira, canafístula and catingueira were subjected to different treatments to overcome dormancy: T1- Control, T2- Scarification and T3 - Scarification + immersion in water for 24 hours. Site visits were carried out daily to determine the number of emerged seeds. With these data, the following were obtained: the emergency speed index (IVE), emergency speed (VE) and the emergency percentage (PE). After 30 days of sowing, biometric analysis was carried out where the parameters were obtained: number of leaves (NF), seedling height (ALT) and stem diameter (DC). Mechanical scarification at the opposite end of the hilum increased the rate of emergence of aroeira, canafístula and catingueira. In the case of biometric parameters, the observed responses were more associated with the intrinsic characteristics of the species analyzed. These results are important to subsidize the production of seedlings and their establishment, maximizing natural resources and reducing costs.